Gamified Digital Tools in Arabic Language Instruction: The Case of Froggy Jumps in an Indonesian Secondary Islamic School - Putri, Tarisha; Sahkholid Nasution, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study investigates the implementation of Froggy Jumps, a gamified digital platform, in enhancing students’ motivation to learn Arabic at an Indonesian secondary Islamic school. The research was conducted using a qualitative case study approach involving eighth-grade students and their Arabic teacher. Data were collected through classroom observations, interviews, and documentation. The findings reveal that Froggy Jumps positively influenced classroom dynamics, increased student engagement, and stimulated learning interest. The gamified elements; points, levels, challenges, audio, and visual features, contributed to a more interactive and enjoyable learning experience. However, the implementation was also influenced by several contextual factors, including internet stability, access to digital devices, and classroom management. The study concludes that while Froggy Jumps is a promising instructional tool, its effectiveness depends on adequate infrastructure, teacher readiness, and responsive pedagogical strategies. Further research using quantitative or mixed methods is recommended to evaluate its impact on student learning outcomes more comprehensively.